Assessing the Usage of Chatgpt among College Students in Kathmandu - Shah, Sadikshya; Pradhan, Sumit (Nepalese Journal of Economics, 2025)
The study examines the usage of ChatGPT among college students in Kathmandu. Usage of ChatGPT is taken as a dependent variable. The selected independent variables are perceived ease of use, usefulness of ChatGPT, peer influence, social influence on ChatGPT, technological proficiency and access to internet. The primary source of data is used to assess the opinions of respondents regarding perceived ease of use, usefulness of ChatGPT, peer influence, social influence on ChatGPT, technological proficiency and access to internet. The study is based on primary data of 208 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of usage of ChatGPT among college students in Kathmandu. The study demonstrated a positive impact of perceived ease of use with the usage of ChatGPT in Kathmandu. It indicates that when respondents find ChatGPT and its features easy to use, they are more likely to increase their usage of ChatGPT. Similarly, the study revealed a positive impact of usefulness of ChatGPT on usage of ChatGPT. It indicates that respondents who perceive ChatGPT as useful tool tend to increase the usage of ChatGPT. Likewise, the study showed a positive impact of peer influence with the usage of ChatGPT. It indicates that increase in peer influence leads to increase in usage of ChatGPT. Further, the study observed a positive impact of social influence on ChatGPT with the usage of ChatGPT. It indicates that increment in social influence leads to the increase in usage of ChatGPT. In addition, the study found a positive impact of technological proficiency with the usage of ChatGPT. It indicates that higher levels of technological proficiency lead to the increase in usage of ChatGPT. Moreover, the study identified a positive impact of access to internet with the usage of ChatGPT. It indicates that improvement in access to internet leads to the increase in usage of ChatGPT. Overall, these findings underscore the significant role of perceived ease of use, usefulness of ChatGPT, peer influence, social influence on ChatGPT, technological proficiency and access to internet in shaping college students’ usage of ChatGPT in Kathmandu.